THE STRATEGY OF CLASICAL GUITAR TRAINING SHOWN BY JEKSON PONTOMUDIS FOR THE EVENT OF FLS2N - Geryanto F. Sasela; Perry Rumengan; Franklin Dumais (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research aims to explore the classical guitar learning strategies applied by Jekson Pontomudis as part of his preparation for the National Student Art Competition Festival (FLS2N). The main focus of this research is to identify the challenges faced in the implementation of Jekson Pontomudis' classical guitar learning strategy in the context of FLS2N preparation. The research method used is qualitative with a musicology approach. Data were collected through observation, interview, and documentation. The results show that this learning strategy faces obstacles, such as the lack of teachers and trainers with classical guitar expertise, as well as limited learning facilities and infrastructure. In addition, the lack of curriculum compatibility with FLS2N demands and inadequate school conditions are problems. To overcome this, it is necessary to improve the qualifications of teaching staff, improve facilities and infrastructure, and evaluate and adjust the curriculum. This research provides insights into the constraints of classical guitar learning strategies in preparation for national competitions, such as FLS2N, and provides a basis for improving the effectiveness of similar learning in other schools.